Comparative Evaluation of Real-Time PCR Methods for Human Noroviruses in Wastewater and Human Stool - Masago, Yoshifumi (PLoS One, 2016)
Selecting the best quantitative PCR assay is essential to detect human norovirus genome effectively from clinical and environmental samples because no cell lines have been developed to propagate this virus. The real-time PCR methods for noroviruses GI (4 assays) and GII (3 assays) were evaluated using wastewater (n = 70) and norovirus-positive stool (n = 77) samples collected in Japan between 2012 and 2013. Standard quantitative PCR assays recommended by the U.S. Environmental Protection Agency, International Organization for Standardization, and Ministry of Health, Labour and Welfare, Japan, together with recently reported assays were included. Significant differences in positive rates and quantification cycles were observed by non-parametric analysis. The present study identifies the best assay for norovirus GI and GII to amplify norovirus genomes efficiently.